2013
DOI: 10.1016/j.jaap.2012.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic pyrolysis of rice husk for bio-oil production

Abstract: Catalytic pyrolysis experiments have been carried out on Brunei Rice Husk (BRH) to obtain bio-oil using a fixed-bed pyrolysis rig. ZSM-5, Al-MCM-41, Al-MSU-F and Brunei rice husk ash (BRHA) were used as the catalysts for the catalytic pyrolysis experiments and comparison was done to analyse the changes in the bio-oil properties and yield. Properties of the liquid catalytic and non-catalytic bio-oil were analysed in terms of water content, pH, acid number, viscosity, density and calorific value. The bio-oil che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
104
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(130 citation statements)
references
References 43 publications
12
104
0
5
Order By: Relevance
“…Acidity (pH) of the oil was between 2.92 and 3.20. This is an indication that the oil may contain substantial amount of organic acids [24] [25]. Water content of the oil varied from 39.28 -43.0 wt% which was mainly due to product of dehydration during pyrolysis reaction [26].…”
Section: Pyrolysis Products Distribution and Characteristicsmentioning
confidence: 99%
“…Acidity (pH) of the oil was between 2.92 and 3.20. This is an indication that the oil may contain substantial amount of organic acids [24] [25]. Water content of the oil varied from 39.28 -43.0 wt% which was mainly due to product of dehydration during pyrolysis reaction [26].…”
Section: Pyrolysis Products Distribution and Characteristicsmentioning
confidence: 99%
“…Most of the time, the catalysts are supported on alumino-silicate structures, like zeolites [2]. Catalysts can be mixed with the biomass within the reactor [3], or placed in a fixed-bed at the outlet of the pyrolysis reactor [4], or used as a bed material in fluidised bed reactors [5]. Pyrolysis of metal salt impregnated biomass has also been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al found that ZSM-5 catalyst increased the aromatic hydrocarbon content from 0.72%, obtained by non-catalytic pyrolysis of Douglas-fir, to 6.89% [33]. Moreover, increasing of aromatic hydrocarbon by about 50% from non-catalytic pyrolysis was achieved in rice husk pyrolysis by using ZSM-5 as catalyst [8] Aromatisation reaction may be preceded by the DielsAlder reaction, in which cyclic and aromatic compounds are produced by cracking combine with each other as shown in Equation 1 [34]. C-C bonds cracking are promoted by strong acidity and shape selectivity of ZSM-5.…”
Section: Catalystmentioning
confidence: 99%
“…Instead of catalytic upgrading of bio-oil, the addition of catalyst during the pyrolysis process was proposed as the alternative pathway to enhance the biooil properties. The direct use of catalysts could decrease the pyrolysis temperature, increase the conversion of biomass and the yield of bio-oil, and change the distribution of the pyrolytic liquid products then improve the quality of the bio-oil obtained [5]- [8].…”
Section: Introductionmentioning
confidence: 99%